Konsep Dasar dan Ruang Lingkup Manajemen Pendidik Dan Tenaga Kependidikan - Basri, Hasan; Afriza, Afriza; Nurhayuni, Nurhayuni; algusyairi, Parisyi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is to integrate Islamic management principles in the management of educators and education personnel in order to improve the quality and effectiveness of education. This research uses the library research method to explore and analyze literature from various written sources such as books, journals, articles, dissertations and official documents regarding the management of educators and education personnel, with the aim of understanding existing theories and identifying gaps in the literature. Data was collected through literature searches in academic databases, selection of credible sources, organizing data based on themes, and analysis by reducing, presenting, and synthesizing information to draw conclusions that can improve the quality and effectiveness of educational management. The result of this work is that educators, including teachers, lecturers and counselors, have an important role in the educational process with the main task of teaching, educating and guiding students, while educational staff such as tutors and instructors support the implementation of education through technical tasks. The management of educators and education personnel is based on Islamic teachings which emphasize skill, discipline and good implementation of tasks, as well as the principle of order to achieve organizational goals. The aim of this management is to ensure that the institution has a quality workforce, an effective work system and a harmonious work climate through recruitment, fair compensation and employee capacity development. Management covers critical aspects such as curriculum, personnel, classes, student affairs, and finance, with duties and functions that emphasize professionalism to improve the quality of education. Even though it is formally recognized, Islamic educational institutions in Indonesia still face quality challenges due to limited facilities and the government's unpreparedness.